Characterization of the Exometabolome of Nitrosopumilus maritimus SCM1 by Liquid Chromatography–Ion Mobility Mass Spectrometry - Law, Kai P.; He, Wei; Tao, Jianchang; Zhang, Chuanlun (Frontiers in Microbiology, 2021)
Marine Thaumarchaeota (formerly known as the marine group I archaea) have received much research interest in recent years since these chemolithoautotrophic organisms are abundant in the subsurface ocean and oxidize ammonium to nitrite, which makes them a major contributor to the marine carbon and nitrogen cycles. However, few studies have investigated the chemical composition of their exometabolome and their contributions to the pool of dissolved organic matter (DOM) in seawater. This study exploits the recent advances in ion mobility mass spectrometry (IM-MS) and integrates this instrumental capability with bioinformatics to reassess the exometabolome of a model ammonia-oxidizing archaeon, Nitrosopumilus maritimus strain SCM1. Our method has several advantages over the conventional approach using an Orbitrap or ion cyclotron resonance mass analyzer and allows assignments or annotations of spectral features to known metabolites confidently and indiscriminately, as well as distinction of biological molecules from background organics. Consistent with the results of a previous report, the SPE-extracted exometabolome of N. maritimus is dominated by biologically active nitrogen-containing metabolites, in addition to peptides secreted extracellularly. Cobalamin and associated intermediates, including α-ribazole and α-ribazole 5′-phosphate, are major components of the SPE-extracted exometabolome of N. maritimus. This supports the proposition that Thaumarchaeota have the capacity of de novo biosynthesizing cobalamin. Other biologically significant metabolites, such as agmatidine and medicagenate, predicted by genome screening are also detected, which indicates that Thaumarchaeota have remarkable metabolic potentials, underlining their importance in driving elemental cycles critical to biological processes in the ocean.